Handbook for research in cooperative education and internships - Linn, Patricia L.; Howard, Adam; Miller, Eric, 1957- (L. Erlbaum Publishers, 2004)
This Handbook is designed to help cooperative education and internship professionals and employers design, carry out, and disseminate quality research and evaluation studies of work-based education. It offers examples of current, leading-edge studies about work-based education, but with a practical twist: The chapter authors frame their studies within a specific key research design issue, including finding a starting point and a theoretical framework; fitting research into one's busy practitioner workload; deciding on particular data-gathering methods and an overall methodological approach; integrating qualitative and quantitative methodologies; and disseminating results. Also addressed are questions and concerns that are relevant throughout the course of a research project: the use of theory in research; the role and relationship of program assessment to research; and ethical considerations in research.